CHANGES OF BLOOD PRESSURE DURING ORTHOSTATISM AND ITS HEMODYNAMIC PROFILE IN PATIENTS IN DIALYSIS. (June 2018) - Schiavone, M.A.; Castellaro, C.; Biain, M.; Magenta, M.; Laham, G.; Calegari, C.; Diaz, C.; Speranzoni, F.; Montagnana, J.; Pereira Redondo, J.C.
Abstract : Objective: 1- Analyze whether increases/decreases in BP during orthostatism are associated with characteristic hemodynamic profiles at rest 2-To establish whether increases/decreases in BP during orthostatism are associated with specific hemodynamic changes by standing 3-Determine independent hemodinamic predictors of orthostatic hypotension and hypertension Design and method: We studied 74 patients within a program of cardiovascular evaluation of patients on dialysis of CEMIC (PRECADIA). BP and hemodynamics were determined by impedance cardiography in the supine position and after the third minute of standing. Patients were classified into 3 groups according to the presence of orthostatic hypotension, orthostatic hypertension and stable behavior of blood pressure. The hemodynamic variables were analyzed according to: 1- basal conditions and 2-differences (Delta standing-lying), in each of them, according to the pressure changes with standing (ANOVA, Tukey). Iindependent hemodynamic predictors for orthostatic hypotension and orthostatic hypertension were determined. Results: In the supine position, the HypertOrt group was significantly younger (p = 0.018), SBP and DBP much lower (p = 0.00067andp = 0.05). I also present significantly less ejection period than the other two groups, accompanied by a tendency to a higher heart rate (p = 0.06). The HipotOrt group presented SBP and DBP significantly higher than the other two groups. Before standing, the HipotOrt group showed a general fall of the Delta-SVRI (p = 0.0182). The HypertOrt group, on the other hand, presented a greater increase Delta-SVRI. There were no significant differences in volume changes as well as in heart rate. In the logistic regressions, SBP turned out to be the only hemodynamic variable predictive of orthostatic hypotension (Odds ratio = 1.0288, p = 0.0019). Predictors of orthostatic hypertension were age (OR = 0.922, 95% CI = 0.8669–0.9802) and SBP (OR = 0.958, p = 0, 0001). Conclusions: In basal conditions, patients with orthostatic hypotension showed a typical profile of supine hypertension-orthostatic hypotension, with a fall in vascular resistance during standing, commonly associated with dysautonomia. The orthostatic hypertension group presented a hyperdynamic tendency, with an increased heart rate with a lower ejection period, this associated with a greater increase in resistance during standing. This would justify the increase in blood pressure when standing.